Industrial Development and the Convergence Question - Goodfriend, Marvin; McDermott, John (American Economic Review, 1998)
This paper studies endogenous world balanced-growth equilibria in which national learning productivity differentials govern relative per capita products. Learning productivities depend on the national share of world specialized-goods production, national and world scale, and familiarity with the foreign economy. Familiarity indexes the extent to which imported specialized goods enhance learning productivity. We find that mutual familiarization causes per capita products to converge. Unfamiliar economies diverge substantially and persistently. Unilateral familiarization of a less-developed country (LDC) with the leading economy causes the LDC to catch up to, and even overtake, the leader.